Breaking the ice with a joke: The relief-inducing property of humor and its effect on sellers' performance. (June 2021) - Lunardo, Renaud; Bompar, Laurent; Saintives, Camille
Research has identified humor as a communication technique that can help sellers be more effective during their sales pitches. However, the most developed theory of humor – that is, the arousal-safety (or relief) theory – posits some relieving power of humor but has never been applied to the selling context, although such a power could reveal interesting for sellers. Therefore, in this research, we adopt a seller's perspective and apply this theory to investigate how sellers' feelings of relief following their use of humor can positively affect their performance during negotiations. More specifically, we investigate the serial process whereby feelings of relief that emerge from humor increase relationship quality and ultimately performance. Finally, we identify empathy as a boundary condition for the effects of humor and subsequent responses, with humor prompting greater feelings of relief when sellers have little empathy with the purchaser. Using a sample of 200 trained students in B2B sales management and a sample of 157 professional sellers, we empirically test and support these predictions, which serve as a basis for managerial recommendations.